A Comparative and Evaluative Study of Two Cytological Grading Systems in Breast Carcinoma with Histological Grading: An Important Prognostic Factor - Pinki Pandey; Alok Dixit; Subrat Chandra; Swarn Kaur (Analytical Cellular Pathology)
Objective. Cytonuclear gradings in the breast carcinoma raise the level of FNA reportage and improves patient management. Our aim was to evaluate and compare two cytological grading methods (Robinson’s and Mouriquand’s) in breast carcinoma and correlate it with Nottingham modification of Scarff-Bloom-Richardson (SBR) histological grading. Materials and Methods. 30 cytologically proven cases of infiltrating ductal carcinoma were graded cytologically and histologically. Cytograding was done by Robinson’s and Mouriquand’s methods (grades I to III) followed by comparison of the two methods. Cytogradings were correlated with SBR grading method. Sensitivity, specificity, diagnostic accuracy, and concordance and discordance rates were evaluated. Results. An overall concordance of 76.66% between cytogradings, of 83.33% between Robinson’s method and SBR, and of 66.66% between Mouriquand’s method and SBR was seen. Robinson’s method correlated best with SBR in all the three nuclear grades. Robinson’s method showed a diagnostic accuracy of 90% with 91.30% sensitivity while Mouriquand’s method had an accuracy of 76.66% with 95.65% sensitivity. The specificity by Mouriquand’s method was quite low (14.28%) as compared to Robinson’s method (85.71%). Conclusion. Comprehensive cytological grading of breast cancer by Robinson’s method seems better because of more objective set of criteria, easy reproducibility, and specificity.